Meloxicam Carrier Systems Having Enhanced Release and Aqueous Wettability Prepared Using Micro-suspensions in Different Liquid Media - Marinko, Nikita; Zámostný, Petr (AAPS PharmSciTech, 2020)
One of the conventional methods of alleviating the problem of poor drug solubility is the particle size reduction. The efficiency of this approach depends on successful formulation suppressing the drug agglomeration. The aim of this study was to circumvent the dissolution problems of model hydrophobic meloxicam drug (MLX) by using liquid media of different wetting capacity to comminute and formulate a rapidly dissolving carrier system without the use of surfactants. Micro-suspensions of MLX were prepared by ball milling, using water or n-Heptane as a liquid medium. The suspensions were used as granulation liquids to formulate granulate from microcrystalline cellulose and lactose mixture. The release kinetics from prepared granulates were studied using the USP-4 dissolution apparatus. Micro-suspensions prepared via wet milling in non-water liquid media exhibited a massive improvement of release rate compared with source meloxicam and they outperformed their water-milled counterparts. The release rates from those formulations, despite not comprising any surfactant, were comparable to those obtained by different authors using surfactant stabilized nanosuspension formulations. Thus, they can present an interesting formulation alternative for hydrophobic drugs that are dissolution limited.
Keywords: Kinetics; Solubility; Lactose; Particle Size; meloxikam; nanostruktury; Suspensions; celulosa; velikost částic; Cellulose; laktosa; suspenze; uvolňování léčiv; Nanostructures; Drug Carriers; Drug Liberation; povrchově aktivní látky; rozpustnost; kinetika; Meloxicam; nosiče léků; Surface-Active Agents